Time‐dependent wavepacket diffusion method and its applications in organic semiconductors. Issue 9 (2nd December 2014) - Han, Lu; Ke, Yaling; Zhong, Xinxin; Zhao, Yi
Abstract : Although the carriers in organic semiconductors commonly follow the hopping‐type motions caused by strong carrier‐phonon interactions, they can also present a band‐like behavior in well‐performed organic crystals. In this article, we review a unified model to describe the carrier dynamics covering from the hopping‐type to band‐like motions, the time‐dependent wavepacket diffusion method proposed in our group recently. In the method, the effects of vibrational motions of organic molecules and inter or intramolecular electronic couplings are considered as the fluctuations to the carrier dynamics. Numerical simulations demonstrate that the computational cost of present method is similar to that of mixed quantum‐classical methods, but it overcomes the deficiency in those methods that the detailed balance principle is not satisfied. We further present how to combine electronic structure calculations and molecular dynamics simulations with the present model to reveal the carrier dynamics in realistic organic semiconductors. © 2014 Wiley Periodicals, Inc. Abstract : In organic materials, the carrier‐phonon interaction plays an important role for the carrier transport process. The time‐dependent wavepacket diffusion (TDWPD) method has been developed to model carrier dynamics from coherent band‐like to hopping‐type regimes. The results demonstrate that TDWPD can accurately predict the carrier dynamics of systems from small compounds to nanoscale materials including thousands of molecules. TDWPD can be effectively combined with electronic structure calculations and tackle realistic models of organic semiconductors.